2008
DOI: 10.1073/pnas.0803557105
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ablation of tumor cells with antibody-functionalized single-walled carbon nanotubes

Abstract: Single-walled carbon nanotubes (CNTs) emit heat when they absorb energy from near-infrared (NIR) light. Tissue is relatively transparent to NIR, which suggests that targeting CNTs to tumor cells, followed by noninvasive exposure to NIR light, will ablate tumors within the range of NIR. In this study, we demonstrate the specific binding of antibody-coupled CNTs to tumor cells in vitro, followed by their highly specific ablation with NIR light. Biotinylated polar lipids were used to prepare stable, biocompatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
273
0
7

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(285 citation statements)
references
References 30 publications
5
273
0
7
Order By: Relevance
“…Success in similar systems by no means implies success in vivo, but if targeting is not observed in relevant fluids, apparent targeting in vivo may be a consequence of other poorly understood phenomena. Indeed, we may generalize these comments, beyond the focus of these experiments, since binding to cells or tissue components (rather than uptake) may be sufficient prior to thermal ablation 34,35 or other therapeutic strategies. Such cases also could benefit from a comparable in situ binding analysis as discussed here.…”
mentioning
confidence: 99%
“…Success in similar systems by no means implies success in vivo, but if targeting is not observed in relevant fluids, apparent targeting in vivo may be a consequence of other poorly understood phenomena. Indeed, we may generalize these comments, beyond the focus of these experiments, since binding to cells or tissue components (rather than uptake) may be sufficient prior to thermal ablation 34,35 or other therapeutic strategies. Such cases also could benefit from a comparable in situ binding analysis as discussed here.…”
mentioning
confidence: 99%
“…The success of this technique depends heavily on the surgeon's accuracy when inserting the catheter. By using targeted nanotubes and the aforementioned properties of these when exposed to near infra-red (NIR) light, more accurate, reliable thermal ablation is achievable without requiring an incision Chakravarty et al, 2008).…”
Section: Drug Targetingmentioning
confidence: 99%
“…2 In the past, there have been numerous experimental studies performed in vitro and in vivo using antibody-functionalized CNTs loaded with chemotherapeutic agents. 2,[77][78][79] It has been suggested that CNTs could be used as nanocarriers for delivering drugs into the body via intravenous routes. 80 Drugs can either attach to the outer surface of CNTs via functional groups or be loaded inside the CNTs.…”
Section: Drug Delivery Via Carbon Nanotubesmentioning
confidence: 99%